2007
DOI: 10.1063/1.2430627
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical characterization of xBiScO3–(1−x)BaTiO3 thin films

Abstract: Using a tolerance factor approach, it was predicted that xBiScO3–(1−x)BaTiO3 will have a morphotropic phase boundary that should enhance both the polarizability and permittivity, relative to the BiScO3 end member, near a composition of x=0.4. To verify this prediction, pulsed laser deposition was used to grow xBiScO3–(1−x)BaTiO3 thin films on (100) SrRuO3∕LaAlO3 and Pt-coated Si substrates. Typical growth conditions were 700°C and 100mTorr O2∕O3. The perovskite structure was found to be stable for compositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 19 publications
7
52
1
Order By: Relevance
“…A single, very diffuse relaxor r-T response occurred for compositions around x = 0.2BS: this gave rise to near-stable r values, 800-1000 over a wide temperature range [20]. Similar behaviour had previously been observed in thin film samples [21]. For x = 0.3 bulk ceramics, values of r ~ 1000 were recorded from temperatures of 0 to 300ºC, with high electrical resistivity, ~ 10 12 cm at 250ºC.…”
Section: Batio3-bisco3supporting
confidence: 54%
“…A single, very diffuse relaxor r-T response occurred for compositions around x = 0.2BS: this gave rise to near-stable r values, 800-1000 over a wide temperature range [20]. Similar behaviour had previously been observed in thin film samples [21]. For x = 0.3 bulk ceramics, values of r ~ 1000 were recorded from temperatures of 0 to 300ºC, with high electrical resistivity, ~ 10 12 cm at 250ºC.…”
Section: Batio3-bisco3supporting
confidence: 54%
“…Recently, Tinberg et al reported ferroelectric thin films based on the BiScO 3 -BaTiO 3 binary system. 12 Similar to the BiScO 3 -PbTiO 3 system, when PbTiO 3 was replaced with BaTiO 3 , the perovskite structure was stabilized and a MPB was observed. Although there are no reports related to the Bi͑Zn 1/2 Ti 1/2 ͒O 3 -BaTiO 3 system, an increased transition temperature can be expected for this system.…”
Section: Introductionmentioning
confidence: 88%
“…The low temperature dependence of the dielectric properties for the pseudocubic phase is in good agreement with previous reports for sintered bodies formed using BaTiO 3 -BiMO 3 solid solutions. [13][14][15][16][17][18][19] This is considered to be related to the relaxed behavior of these solid solutions, and the diffused temperature dependence of ε r , which reduces the overall temperature dependence of ε r . 20 In contrast, Mitsui et al reported that the maximum ε r was observed at more than 400 • C for x = 0.60.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Also, a low ε r temperature dependence has been reported for solid solution systems of BaTiO 3 and Bi-based perovskite oxides with pseudocubic structures at room temperature. Sintered bodies of BaTiO 3 -BiMO 3 [where M = Sc 3+ , Al 3+ , (Mg 0.5 Ti 0.5 ) 3+ , and (Zn 0.5 Ti 0.5 ) 3+ ] with pseudocubic symmetry show particularly high ε r stability at temperatures up to 400 • C. [13][14][15][16][17][18][19] In a previous study, we investigated the dielectric properties of ternary BaTiO 3 -Bi(Mg 0.5 Ti 0.5 )O 3 -BiFeO 3 solid solution films prepared by chemical solution deposition (CSD) as alternatives to BaTiO 3 -based high-ε r materials. 20 This system has a wide compositional region with a pseudocubic symmetry between the tetragonal and rhombohedral symmetries at room temperature.…”
Section: Introductionmentioning
confidence: 99%